North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Fifty years of riverine harmful algal bloom modeling: A global synthesis of approaches, challenges, and opportunities - Jennifer C. Murphy; Rebecca M. Gorney; Lisa V. Lucas; Jacob A. Zwart; Jennfier L. Graham (Water Research, 2026)

Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Bridging the data gap: Integration of spatial modelling in wildlife disease surveillance - Sara R. Wijburg; Hein Sprong; Jolianne M. Rijks; Andrea Gröne; Joaquín Vicente Baños; Egil A.J. Fischer; Graham C. Smith; Miriam Maas (Ecological Modelling, 2026)

Mantle compositional architecture and diamond potential of the Alto Paranaíba Igneous Province, Brazil: Insights from garnet xenocryst compositions in kimberlites - Julia C. Bandeira; Rogério G. Azzone; Luanna Chmyz; D. Graham Pearson; Izaac Cabral-Neto; Excelso Ruberti; Vincenza Guarino; Luísa D.V. Carvalho; Qiwei Zhang; Chiranjeeb Sarkar; Lina M. Cetina; Antônio Vítor Braga do Espírito Santo (Lithos, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dynamic trajectories and maturity of farmer collaboration for biodiversity sensitive farming – Insights from the FRAMEwork Farmer Clusters - Iris C. Bohnet; Gerid Hager; Thomas Rellensmann; Claire Hardy; Niamh M. McHugh; Daniela Ablinger; Virginia Bagnoni; Gillian Banks; Marco Beyer; Lennard Duijvestijn; Pierre Franck; Kristina Janeckova; et al. (Agricultural Systems, 2026)

Are Insect Populations Inherently More Variable? A Multi‐Taxa Approach to Characterising Interannual Fluctuations in Insect Time Series - Graham A. Montgomery; Eliza M. Grames; Jake M. Jacobsen; Ethan X. Kahn; Amanda Leyel; Mia C. Rosati; Qiyuan Wu; Chris S. Elphick; David Wagner; Morgan W. Tingley (Ecology Letters, 2026)
The determinants of population variability across taxa, time, and space are not fully understood, particularly for insects, a group with recent reports of widespread abundance declines. We collated data from unpublished and published sources to calculate indices of interannual population variability for over 4500 unique insect time series, comprising data from nearly 1500 species. We evaluate whether insects exhibit greater population variability than other types of animals. Our results demonstrate that insects as a group indeed exhibit much greater population variability than birds, mammals, or fish, but that within Insecta, included orders show similar levels of population variability. We also find that population variability in insects is greater at higher latitudes, for species with smaller body sizes and for shorter, older time series and that it varies between biomes. Overall, our findings can inform the interpretation and prediction of insect population trends, fluctuations and extinction risk in an era of insect decline.

Detrital minerals indicate hidden reservoirs to a REE-mineral placer in Westland, New Zealand - Hayden Dalton; Marshall C. Palmer; Nadine P. Cooper; Andrew J. Locock; Yan Luo; D. Graham Pearson; Orion K.W. Marshall; Petrus J. le Roux; Thomas W. Ritchie; Joshua J. Schwartz; Tingting Wang; Sarah Woodland; et al. (Lithos, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

DNA methylation-based surrogate markers of C-reactive protein and their associations with health-related traits - Danmeng Lily Li; Allison M. Hodge; Joanne Ryan; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2026)
Several methylation-based surrogate markers of C-reactive protein ( mCRP ) have been proposed and used to assess the risk of age-related phenotypes and construct novel ageing markers. We aimed to (i) assess the variance in plasma CRP explained by several mCRP markers; (ii) compare their associations with three health-related traits: mortality, body mass index (BMI), and PCGrimAge ; and (iii) assess the stability of CRP and mCRP over a decade. Blood samples were collected from 947 participants in the Melbourne Collaborative Cohort Study at baseline (1990–1994) and wave 2 (2003–2007). High-sensitivity CRP was measured in plasma samples. Five mCRP markers were calculated: mCRP-Ligthart , mCRP-Wielscher , mCRP-EpiScore , mCRP-GrimAge2 , and mCRP-Hillary . Intraclass correlation coefficients (ICCs) were calculated to assess the stability of CRP/ mCRP between baseline and wave 2. Associations of wave 2 CRP/ mCRP with mortality ( N deaths = 319) were assessed using Cox models and linear regression for BMI and age-adjusted PCGrimAge . mCRP explained 6.0% ( mCRP-Wielscher ) to 16.8% ( mCRP-GrimAge2 ) of the variance in plasma CRP. The ICCs for CRP and mCRP markers were similar, ranging from 0.44 ( mCRP-GrimAge2 ) to 0.63 ( mCRP-Wielscher ). Compared with CRP, mCRP had stronger associations with PCGrimAge , whereas for mortality and BMI, the associations were similar or weaker for mCRP . Associations between mCRP and mortality were greatly attenuated after adjusting for PCGrimAge but less so after adjusting for CRP. The association of CRP with mortality remained strong after adjusting for mCRP . Our study validated mCRP markers and clarified the role of CRP and mCRP in ageing, which may inform the use and development of ageing biomarkers.

Aspects of Germanium and Nickel accumulation in low-ash coal: Examples from the Blue Gem coal, eastern Kentucky, USA - James C. Hower; Susan M. Rimmer; Darrell N. Taulbee; Debora Berti; Robert B. Finkelman; David French; Ian T. Graham; Harold H. Schobert; Lei Zhao; Shifeng Dai (International Journal of Coal Geology, 2026)

Corallivorous Fish Have Reduced Population Sizes and Altered Foraging Behaviour on a Recently Restored Coral Reef - Timothy A. C. Lamont; Permas B. Maulana; Ines D. Lange; Muhammad Rizky Madjid; Andi M. A. Pratama; Cicilia V. Parrangan; Tries B. Razak; Nicholas A. J. Graham (Global Change Biology, 2025)
Ecosystem restoration is a global priority for biodiversity recovery. However, many restoration efforts to date focus only on planting target species, without evaluating the resulting ecosystem‐level impacts on community development and trophic networks. For example, most of the world's efforts to restore tropical coral reefs have evaluated only the recovery of coral organisms. Here, we investigate the re‐establishment of different trophic groups of reef fishes in response to rapid coral recovery at one of the world's largest coral restoration projects. Within 4–6 years of coral restoration starting, coral cover returned to levels found at nearby healthy reference sites. Many groups of fishes recovered similarly quickly; herbivores, planktivores and omnivores recovered abundances equivalent to reference sites within the same time frame. However, although corallivorous fish abundance on 4–6‐year‐old restored reefs was significantly higher than on degraded reefs, it remained at just half the abundance of nearby healthy reference sites. Feeding observations demonstrated that across both healthy and restored habitat, the system's most abundant obligate corallivore (the butterflyfish Chaetodon octofasciatus ) consistently targeted a small subset of corals—82% of all recorded bites were on just seven coral morphotaxa. Several of these targeted coral morphotaxa were significantly less abundant on restored reefs than on healthy reference sites. Despite reduced availability of these comparatively rare corals on restored reefs, butterflyfish maintained their dietary preferences, meaning that they exhibited a higher dietary selectivity and foraged over areas twice as large compared to healthy reefs. This demonstrates that despite a rapid recovery of coral cover and some fish groups, the reduced recovery rates of slower‐growing coral morphotaxa limit the speed at which specialist corallivores can re‐establish. Restored coral reefs may regain their coral cover within 5 years, but they will require longer time frames to achieve full trophic networks and ecological complexity.

In situ Rb–Sr dating and REE analysis of glauconites and detrital feldspars from the Ediacaran/Cambrian strata: Centralian and Adelaide Superbasins, Australia - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Sarah E. Gilbert; Charles Verdel; Stefan C. Löhr; Glenn A. Brock; Graham A. Shields; Andre Baldermann; Ahmad Redaa; Morgan Blades; Darwinaji Subarkah; et al. (Precambrian Research, 2025)

The University of Oklahoma Inpatient Spine Protocol: optimizing surgical outcomes through standardized perioperative care - David Barkyoumb; William C. Kaiser; Lonnie Smith; Lance M. Villeneuve; Graham Mulvaney; Chao Li; Christopher S. Graffeo; Andrew M. Bauer; Hakeem J. Shakir; Karl Balsara; M. Burhan Janjua; John F. Burke; et al. (GeroScience, 2025)

Monsoonal influence on floating marine litter pathways in the Bay of Bengal - Lianne C. Harrison; Jennifer A. Graham; Piyali Chowdhury; Tiago A. M. Silva; Danja P. Hoehn; Alakes Samanta; Kunal Chakraborty; Sudheer Joseph; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Ocean Science, 2025)
Marine litter in the Bay of Bengal has been under-studied despite large quantities of mismanaged waste reportedly entering the ocean from its surrounding countries. The seasonal reversal of monsoon currents in this region provides a unique environment for the transport of floating macro-litter. A particle tracking model is used here to investigate source-to-sink connectivity of marine debris between countries via oceanic pathways in the Bay of Bengal. We use an approach considering uniform release of particles along the entire coastline, avoiding the considerable uncertainties associated with assumed riverine sources. Two different simulations are considered, forced with either a high-resolution ocean hindcast developed specifically for the Bay of Bengal or a lower-resolution dataset which includes data assimilation. The vast majority of particles released during our simulations were found to beach within 16 months; most particles beached in their country of origin (57 %–90 %), with connectivity towards Myanmar accounting for the second highest connectivity rates (2 %–29 %) from many countries within the Bay of Bengal. This is likely due to the relatively large size of Myanmar's coastline and that it lies in the path of the East India Coastal Current for much of the year (February–September). Patterns of connectivity were found to change along with the monsoon and the post-monsoon period (October–January) showed a notably greater dispersal of particles than the rest of the year. Both simulations were evaluated using the pathways of undrogued surface drifters, which moved primarily within the open ocean, with better agreement found here for particles advected by data-assimilated ocean velocities. This study will therefore crucially inform future research and policy in this region, providing advice on the benefits and suitability of selecting different modelling approaches independent of assumptions of the source locations or volumes.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

The response of avian chewing lice (Psocodea: Phthiraptera) loads to early-1900s urbanization in the Western United States - Ethan X. Kahn; Jake M. Jacobsen; Amanda Leyel; Mia C. Rosati; Graham A. Montgomery; Morgan W. Tingley (Urban Ecosystems, 2025)
Urbanization can alter all types of ecological interactions, including parasitism. For urban-associated hosts, two hypotheses predict the response of parasites to urbanization: dense host populations can increase disease transmission, and/or healthy host populations can increase immunity against disease. Using a historical record of bird specimens, we examined the effect of historical urban environments on parasitic interactions by measuring the abundance of ectoparasites on two bird species: House Finch and Hairy Woodpecker. We counted adult chewing lice and their nits from museum study skins of these two species, which were collected in the western United States from 1900 to 1932. Our urbanness metric for each specimen’s collection site and year was extracted from the Built-Up Footprint Area dataset, which measures the area covered by human structures each decade. Despite finding many lice preserved on museum specimens, we found no significant relationship between urbanness and louse loads. This result could be because lice are not sensitive to their external environment, or because the impacts of urbanization on birds were still small in the temporal range documented by our specimens. We also found that House Finches had more nits but fewer adult Ischnocera than Hairy Woodpeckers, and that Ischnocera and nit loads exhibited slight seasonal variation. Our study emphasizes the value of museum collections for understanding the historical process of urbanization in an ecological context, including bird-louse dynamics, and provides an important initial evaluation of how chewing lice may or may not respond to urbanization.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Physical activity and DNA methylation–based markers of ageing in 6208 middle-aged and older Australians: cross-sectional and longitudinal analyses - Haoxin Tina Zheng; Danmeng Lily Li; Makayla W. C. Lou; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Brigid M. Lynch; Pierre-Antoine Dugué (GeroScience, 2024)
Epigenetic age quantifies biological age using DNA methylation information and is a potential pathway by which physical activity benefits general health. We aimed to assess the cross-sectional and longitudinal associations between physical activity and epigenetic age in middle-aged and older Australians. Blood DNA methylation data for 6208 participants (40% female) in the Melbourne Collaborative Cohort Study (MCCS) were available at baseline (1990–1994, mean age, 59 years) and, of those, for 1009 at follow-up (2003–2007, mean age, 69 years). Physical activity measurements (weighted scores at baseline and follow-up and total MET hours per week at follow-up) were calculated from self-reported questionnaire data. Five blood methylation–based markers of ageing ( PCGrimAge , PCPhenoAge , bAge , DNAmFitAge , and DunedinPACE ) and four fitness-related markers ( DNAmGaitspeed , DNAmGripmax , DNAmVO2max , and DNAmFEV1 ) were calculated and adjusted for age. Linear regression was used to examine the cross-sectional and longitudinal associations between physical activity and epigenetic age. Effect modification by age, sex, and BMI was assessed. At baseline, a standard deviation (SD) increment in physical activity was associated with 0.03-SD ( DNAmFitAge , 95%CI = 0.01, 0.06, P = 0.02) to 0.07-SD ( bAge , 95%CI = 0.04, 0.09, P = 2 × 10 −8 ) lower epigenetic age. These associations were attenuated after adjustment for other lifestyle variables. Only weak evidence was found for the longitudinal association ( N = 1009) of changes in physical activity and epigenetic age (e.g. DNAmFitAge : adjusted β = − 0.04, 95%CI = − 0.08, 0.01). The associations were not modified by age, sex, or BMI. In middle-aged and older Australians, higher levels of self-reported physical activity were associated with slightly lower epigenetic age.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Dietary factors and DNA methylation-based markers of ageing in 5310 middle-aged and older Australian adults - Lachlan Cribb; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2024)
The role of nutrition in healthy ageing is acknowledged but details of optimal dietary composition are still uncertain. We aimed to investigate the cross-sectional associations between dietary exposures, including macronutrient composition, food groups, specific foods, and overall diet quality, with methylation-based markers of ageing. Blood DNA methylation data from 5310 participants (mean age 59 years) in the Melbourne Collaborative Cohort Study were used to calculate five methylation-based measures of ageing: PCGrimAge , PCPhenoAge , DunedinPACE , ZhangAge , TelomereAge . For a range of dietary exposures, we estimated (i) the ‘equal-mass substitution effect’, which quantifies the effect of adding the component of interest to the diet while keeping overall food mass constant, and (ii) the ‘total effect’, which quantifies the effect of adding the component of interest to the current diet. For ‘equal-mass substitution effects’, the strongest association for macronutrients was for fibre intake (e.g. DunedinPACE , per 12 g/day − 0.10 [standard deviations]; 95%CI − 0.15, − 0.05, p < 0.001). Associations were positive for protein (e.g. PCGrimAge , per 33 g/day 0.04; 95%CI 0.01–0.08, p = 0.005). For food groups, the evidence tended to be weak, though sugar-sweetened drinks showed positive associations, as did artificially-sweetened drinks (e.g. DunedinPACE , per 91 g/day 0.06, 95%CI 0.03–0.08, p < 0.001). ‘Total effect’ estimates were generally very similar. Scores reflecting overall diet quality suggested that healthier diets were associated with lower levels of ageing markers. High intakes of fibre and low intakes of protein and sweetened drinks, as well as overall healthy diets, showed the most consistent associations with lower methylation-based ageing in our study.

Stable carbon isotopes and bulk-sediment geochemistry as indicators of relative sea-level change in tidal marshes, mangroves and isolation basins: Application and developments - Graham P. Wilson; Jeremy M. Lloyd; Nicole S. Khan; Andrew C. Kemp (Quaternary Science Reviews, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Genomic Mosaicism of the Brain: Origin, Impact, and Utility - Jared H. Graham; Johannes C. M. Schlachetzki; Xiaoxu Yang; Martin W. Breuss (Neuroscience Bulletin, 2024)
Genomic mosaicism describes the phenomenon where some but not all cells within a tissue harbor unique genetic mutations. Traditionally, research focused on the impact of genomic mosaicism on clinical phenotype—motivated by its involvement in cancers and overgrowth syndromes. More recently, we increasingly shifted towards the plethora of neutral mosaic variants that can act as recorders of cellular lineage and environmental exposures. Here, we summarize the current state of the field of genomic mosaicism research with a special emphasis on our current understanding of this phenomenon in brain development and homeostasis. Although the field of genomic mosaicism has a rich history, technological advances in the last decade have changed our approaches and greatly improved our knowledge. We will provide current definitions and an overview of contemporary detection approaches for genomic mosaicism. Finally, we will discuss the impact and utility of genomic mosaicism.

Self-rated health, epigenetic ageing, and long-term mortality in older Australians - Danmeng Lily Li; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2024)
Self-rated health (SRH) is a subjective indicator of overall health based on a single questionnaire item. Previous evidence found that it is a strong predictor of mortality, although the underlying mechanism is poorly understood. Epigenetic age is an objective, emerging biomarker of health, estimated using DNA methylation data at hundreds of sites across the genome. This study aimed to assess the overlap and interaction between SRH and epigenetic ageing in predicting mortality risk. We used DNA methylation data from 1059 participants in the Melbourne Collaborative Cohort Study (mean age: 69 years) to calculate three age-adjusted measures of epigenetic ageing: GrimAge , PhenoAge , and DunedinPACE . SRH was assessed using a five-category questionnaire item (“excellent, very good, good, fair, poor”). Cox models were used to assess the associations of SRH, epigenetic ageing, and their interaction, with all-cause mortality over up to 17 years of follow-up ( N deaths = 345). The association of SRH with mortality per category increase was HR = 1.29; 95%CI: 1.14–1.46. The association was slightly attenuated after adjusting for all three epigenetic ageing measures (HR = 1.25, 95%CI: 1.10–1.41). A strong gradient was observed in the association of GrimAge ( P interaction = 0.006) and DunedinPACE ( P interaction = 0.002) with mortality across worsening SRH strata. For example, the association between DunedinPACE and mortality in participants with “excellent” SRH was HR = 1.02, 95%CI: 0.73–1.43 and for “fair/poor” HR = 1.72, 95%CI: 1.35–2.20. SRH and epigenetic ageing were synergistic risk factors of mortality in our study. These findings suggest that consideration of subjective and objective factors may improve general health assessment, which has implications for the ongoing development of molecular markers of ageing.

Thermal stressors during embryo incubation have limited ontogenic carryover effects in brook trout - Emily R. Lechner; Erin M.C. Stewart; Vince R. Frasca; Ken M. Jeffries; Chris C. Wilson; Graham D. Raby (Journal of Thermal Biology, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Proliferation and anatoxin production of benthic cyanobacteria associated with canine mortalities along a stream-lake continuum - Lindsay H. Johnston; Yannan Huang; Tessa D. Bermarija; Cheryl Rafuse; Lydia Zamlynny; Meghann R. Bruce; Catherine Graham; André M. Comeau; Cecilio Valadez-Cano; Janice E. Lawrence; Daniel G. Beach; Rob C. Jamieson (Science of The Total Environment, 2024)

CT max in brook trout ( Salvelinus fontinalis ) embryos shows an acclimation response to developmental temperatures but is more variable than in later life stages - Emily R. Lechner; Erin M. C. Stewart; Chris C. Wilson; Graham D. Raby (Journal of Fish Biology, 2024)
Critical thermal maximum (CT max ) is widely used to measure upper thermal tolerance in fish but is rarely examined in embryos. Upper thermal limits generally depend on an individual's thermal history, which molds plasticity. We examined how thermal acclimation affects thermal tolerance of brook trout ( Salvelinus fontinalis ) embryos using a novel method to assess CT max in embryos incubated under three thermal regimes. Warm acclimation was associated with an increase in embryonic upper thermal tolerance. However, CT max variability was markedly higher than is typical for juvenile or adult salmonids.

Differences in embryo survivorship among populations of brook trout (Salvelinus fontinalis) under variable winter thermal regimes - Erin M. C. Stewart; Emily R. Lechner; Vince R. Frasca; Chris C. Wilson; Graham D. Raby (Environmental Biology of Fishes, 2024)

Manipulation of the seagrass‐associated microbiome reduces disease severity - Olivia J. Graham; Emily M. Adamczyk; Siobhan Schenk; Phoebe Dawkins; Samantha Burke; Emily Chei; Kaitlyn Cisz; Sukanya Dayal; Jack Elstner; Arjun Lev Pillai Hausner; Taylor Hughes; Omisha Manglani; et al. (Environmental Microbiology, 2024)
Host‐associated microbes influence host health and function and can be a first line of defence against infections. While research increasingly shows that terrestrial plant microbiomes contribute to bacterial, fungal, and oomycete disease resistance, no comparable experimental work has investigated marine plant microbiomes or more diverse disease agents. We test the hypothesis that the eelgrass ( Zostera marina ) leaf microbiome increases resistance to seagrass wasting disease. From field eelgrass with paired diseased and asymptomatic tissue, 16S rRNA gene amplicon sequencing revealed that bacterial composition and richness varied markedly between diseased and asymptomatic tissue in one of the two years. This suggests that the influence of disease on eelgrass microbial communities may vary with environmental conditions. We next experimentally reduced the eelgrass microbiome with antibiotics and bleach, then inoculated plants with Labyrinthula zosterae , the causative agent of wasting disease. We detected significantly higher disease severity in eelgrass with a native microbiome than an experimentally reduced microbiome. Our results over multiple experiments do not support a protective role of the eelgrass microbiome against L. zosterae . Further studies of these marine host–microbe–pathogen relationships may continue to show new relationships between plant microbiomes and diseases.

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

ebony underpins Batesian mimicry in melanic stoneflies - Brodie J. Foster; Graham A. McCulloch; Yasmin Foster; Gracie C. Kroos; Tania M. King; Jonathan M. Waters (Molecular Ecology, 2023)
The evolution of Batesian mimicry – whereby harmless species avoid predation through their resemblance to harmful species – has long intrigued biologists. In rare cases, Batesian mimicry is linked to intraspecific colour variation, in which only some individuals within a population resemble a noxious ‘model’. Here, we assess intraspecific colour variation within a widespread New Zealand stonefly, wherein highly melanized individuals of Zelandoperla closely resemble a chemically defended aposematic stonefly, Austroperla cyrene . We assess convergence in the colour pattern of these two species, compare their relative palatability to predators, and use genome‐wide association mapping to assess the genetic basis of this resemblance. Our analysis reveals that melanized Zelandoperla overlap significantly with Austroperla in colour space but are significantly more palatable to predators, implying that they are indeed Batesian mimics. Analysis of 194,773 genome‐wide SNPs reveals an outlier locus ( ebony ) strongly differentiating melanic versus non‐melanic Zelandoperla . Genotyping of 338 specimens from a single Zelandoperla population indicates that ebony explains nearly 70% of the observed variance in melanism. As ebony has a well‐documented role in insect melanin biosynthesis, our findings indicate this locus has a conserved function across deeply divergent hexapod lineages. Distributional records suggest a link between the occurrence of melanic Zelandoperla and the forested ecosystems where the model Austroperla is abundant, suggesting the potential for adaptive shifts in this system underpinned by environmental change.

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Getting the bugs out of AI : Advancing ecological research on arthropods through computer vision - Stefan Schneider; Graham W. Taylor; Stefan C. Kremer; John M. Fryxell (Ecology Letters, 2023)
Deep learning for computer vision has shown promising results in the field of entomology, however, there still remains untapped potential. Deep learning performance is enabled primarily by large quantities of annotated data which, outside of rare circumstances, are limited in ecological studies. Currently, to utilize deep learning systems, ecologists undergo extensive data collection efforts, or limit their problem to niche tasks. These solutions do not scale to region agnostic models. However, there are solutions that employ data augmentation, simulators, generative models, and self‐supervised learning that can supplement limited labelled data. Here, we highlight the success of deep learning for computer vision within entomology, discuss data collection efforts, provide methodologies for optimizing learning from limited annotations, and conclude with practical guidelines for how to achieve a foundation model for entomology capable of accessible automated ecological monitoring on a global scale.

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

CMIP6 model fidelity at simulating large-scale atmospheric circulation patterns and associated temperature and precipitation over the Pacific Northwest - Graham P. Taylor; Paul C. Loikith; Christina M. Aragon; Huikyo Lee; Duane E. Waliser (Climate Dynamics, 2023)

Cephalopods, a gap in the European Marine Strategy Framework Directive and their future integration - Bianca T. C. Bobowski; Anne Marie Power; Graham J. Pierce; Ana Moreno; Ane Iriondo; Julio Valeiras; Inna M. Sokolova; Daniel Oesterwind (Marine Biology, 2023)
With the aim of maintaining or obtaining good environmental status in the Northeast Atlantic and northern Mediterranean Sea, the European Marine Strategy Framework Directive (EU-MSFD) came into force in 2008. All EU Member States (MS) have the task of assessing the current state of their adjacent waters to guarantee sustainable use of marine resources and healthy ecosystems for the current and future generations. Although the MSFD has been implemented for over a decade, there are still gaps in the assessment of various ecologically and commercially important marine species, such as cephalopods. Here we describe the status of cephalopods, a key component of marine ecosystems and a valuable fishing resource, within the MSFD. To do so, we review how MS deal with this group in their reporting and identify and explain the gaps in the cephalopod assessment. We describe the main challenges including the limited data and the rarity of dedicated surveys on cephalopods. However, we argue that cephalopods can be partially integrated into the EU-MSFD assessment, illustrating the current opportunities and future possibilities of their integration into the MSFD, mainly using Descriptors 1–4. Graphical abstract

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

High frequency UV–Vis sensors estimate error in riverine dissolved organic carbon load estimates from grab sampling - J. P. Ritson; O. Kennedy-Blundell; J. Croft; M. R. Templeton; C. E. Hawkins; J. M. Clark; M. G. Evans; R. E. Brazier; D. Smith; N. J. D. Graham (Environmental Monitoring and Assessment, 2022)
High frequency ultraviolet – visible (UV–VIS) sensors offer a way of improving dissolved organic carbon (DOC) load estimates in rivers as they can be calibrated to DOC concentration. This is an improvement on periodic grab sampling, or the use of pumped sampling systems which store samples in-field before collection. We hypothesised that the move to high frequency measurements would increase the load estimate based on grab sampling due to systemic under-sampling of high flows. To test our hypotheses, we calibrated two sensors in contrasting catchments (Exe and Bow Brook, UK) against weekly grab sampled DOC measurements and then created an hourly time series of DOC for the two sites. Taking this measurement as a ‘true’ value of DOC load, we simulated 1,000 grab sampling campaigns at weekly, fortnightly and monthly frequency to understand the likely distribution of load and error estimates. We also performed an analysis of daily grab samples collected using a pumped storage sampling system with weekly collection. Our results show that: a) grab sampling systemically underestimates DOC loads and gives positively skewed distributions of results, b) this under-estimation and positive skew decreases with increasing sampling frequency, c) commonly used estimates of error in the load value are also systemically lowered by the oversampling of low, stable flows due to their dependence on the variance in the flow-weighted mean concentration, and d) that pumped storage systems may lead to under-estimation of DOC and over estimation of specific ultra-violet absorbance (SUVA), a proxy for aromaticity, due to biodegradation during storage.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes - Lillian R. Aoki; Brendan Rappazzo; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Morgan E. Eisenlord; Olivia J. Graham; Leah Harper; Timothy L. Hawthorne; Margot Hessing‐Lewis; Kevin A. Hovel; Zachary L. Monteith; et al. (Limnology and Oceanography, 2022)
Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass ( Zostera marina ) meadows provide essential coastal habitat and are vulnerable to a temperature‐sensitive wasting disease caused by the protist Labyrinthula zosterae . We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long‐term satellite remote sensing of ocean temperature with field surveys from 32 meadows along the Pacific coast of North America in 2019. Between 11% and 99% of plants were infected in individual meadows, with up to 35% of plant tissue damaged. Disease prevalence was 3× higher in locations with warm temperature anomalies in summer, indicating that the risk of wasting disease will increase with climate warming throughout the geographic range for eelgrass. Large‐scale surveys were made possible for the first time by the Eelgrass Lesion Image Segmentation Application, an artificial intelligence (AI) system that quantifies eelgrass wasting disease 5000× faster and with comparable accuracy to a human expert. This study highlights the value of AI in marine biological observing specifically for detecting widespread climate‐driven disease outbreaks.

Managing fisheries for maximum nutrient yield - James P.W. Robinson; Kirsty L. Nash; Julia L. Blanchard; Nis S. Jacobsen; Eva Maire; Nicholas A.J. Graham; M. Aaron MacNeil; Jessica Zamborain‐Mason; Edward H. Allison; Christina C. Hicks (Fish and Fisheries, 2022)
Wild‐caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutrition‐sensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation for managing fisheries for multispecies Maximum Nutrient Yield (mMNY). We empirically test our approach using size‐based models of North Sea and Baltic Sea fisheries and show that mMNY is predicted by the relative contribution of nutritious species to total catch and their vulnerability to fishing, leading to trade‐offs between catch and specific nutrients. Simulated nutrient yield curves suggest that vitamin D, which is deficient in Northern European diets, was underfished at fishing levels that returned maximum catch weights. Analysis of global catch data shows there is scope for nutrient yields from most of the world's marine fisheries to be enhanced through nutrient‐sensitive fisheries management. With nutrient composition data now widely available, we expect our mMNY framework to motivate development of nutrient‐based reference points in specific contexts, such as data‐limited fisheries. Managing for mMNY alongside policies that promote access to fish could help close nutrient gaps for coastal populations, maximising the contribution of wild‐caught fish to global food and nutrition security.

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Moderation of buprenorphine therapy for cocaine dependence efficacy by variation of the Prodynorphin gene - David A. Nielsen; Robrina Walker; David P. Graham; Ellen M. Nielsen; Sara C. Hamon; Maureen Hillhouse; Dikla Shmueli-Blumberg; William B. Lawson; Kathy Shores-Wilson; Beverlyn D. Settles-Reaves; John Rotrosen; Madhukar H. Trivedi; et al. (European Journal of Clinical Pharmacology, 2022)

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Intradialytic cycling does not exacerbate microparticles or circulating markers of systemic inflammation in haemodialysis patients - Patrick J. Highton; Daniel S. March; Darren R. Churchward; Charlotte E. Grantham; Hannah M. L. Young; Matthew P. M. Graham-Brown; Seila Estruel; Naomi Martin; Nigel J. Brunskill; Alice C. Smith; James O. Burton; Nicolette C. Bishop (European Journal of Applied Physiology, 2022)
Purpose Patients receiving haemodialysis (HD) display elevated circulating microparticle (MP) concentration, tissue factor (TF) expression and markers of systemic inflammation, though regular intradialytic cycling (IDC) may have a therapeutic effect. This study investigated the impact of regular, moderate-intensity IDC on circulating MPs and inflammatory markers in unit-based HD patients. Methods Patients were cluster-randomised to intervention ( n = 20, age: 51.4 ± 18.1 years, body mass: 77.6 ± 18.3 kg, mean ± SD) or no-exercise control ( n = 20, 56.8 ± 14.0 years, 80.5 ± 26.5 kg). Intervention participants completed 30 min of moderate intensity (rating of perceived exertion [RPE] of 12–14) IDC, thrice weekly for 6 months. Pre-dialysis venous blood samples were obtained at 0, 3 and 6 months. Circulating MP phenotypes, cytokines, chemokine and MP TF expression were quantified using flow cytometry and cytometric bead array assays. Results Despite high exercise compliance (82%), no IDC-dependent effects were observed for any MP, cytokine or chemokine measure ( p ≥ 0.051, η ρ 2 ≤ 0.399) other than TNF-α ( p = 0.001, η ρ 2 = 0.186), though no significance was revealed upon post hoc analysis. Conclusion Six months of regular, moderate-intensity IDC had no effect on MPs, cytokines or chemokines. This suggests that the exercise did not exacerbate thrombotic or inflammatory status, though further functional assays are required to confirm this. Trial registration ISRCTN1129707, prospectively registered on 05/03/2015.

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Towards increasing production of genetically improved farmed types in aquaculture - Eric Hallerman; Alexandre Wagner Silva Hilsdorf; Devin M. Bartley; Graham C. Mair (Reviews in Aquaculture, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Human activity shapes the wintering ecology of a migratory bird - Benjamin M. Van Doren; Greg J. Conway; Robbie J. Phillips; Glynne C. Evans; Graham C. M. Roberts; Miriam Liedvogel; Ben C. Sheldon (Global Change Biology, 2021)
Human behavior profoundly affects the natural world. Migratory birds are particularly susceptible to adverse effects of human activities because the global networks of ecosystems on which birds rely are undergoing rapid change. In spite of these challenges, the blackcap ( Sylvia atricapilla ) is a thriving migratory species. Its recent establishment of high‐latitude wintering areas in Britain and Ireland has been linked to climate change and backyard bird feeding, exemplifying the interaction between human activity and migrant ecology. To understand how anthropogenic influences shape avian movements and ecology, we marked 623 wintering blackcaps at 59 sites across Britain and Ireland and compiled a dataset of 9929 encounters. We investigated visitation behavior at garden feeding sites, inter‐annual site fidelity, and movements within and across seasons. We analyzed migration tracks from 25 geolocators fitted to a subset of individuals to understand how garden behavior may impact subsequent migration and breeding. We found that blackcaps wintering in Britain and Ireland showed high site fidelity and low transience among wintering sites, in contrast to the itinerant movements characteristic of blackcaps wintering in their traditional winter range. First‐winter birds showed lower site fidelity and a greater likelihood of transience than adults. Adults that frequented gardens had better body condition, smaller fat stores, longer bills, and rounder wingtips. However, blackcaps did not exclusively feed in gardens; visits were linked to harsher weather. Individuals generally stayed at garden sites until immediately before spring departure. Our results suggest that supplementary feeding is modifying blackcap winter ecology and driving morphological evolution. Supplemental feeding may have multifaceted benefits on winter survival, and these positive effects may carry over to migration and subsequent breeding. Overall, the high individual variability in blackcap movement and foraging ecology, and the flexibility it imparts, may have allowed this species to flourish during rapid environmental change.

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

Creating leadership collectives for sustainability transformations - O. Care; M. J. Bernstein; M. Chapman; I. Diaz Reviriego; G. Dressler; M. R. Felipe-Lucia; C. Friis; S. Graham; H. Hänke; L. J. Haider; M. Hernández-Morcillo; H. Hoffmann; et al. (Sustainability Science, 2021)
Enduring sustainability challenges requires a new model of collective leadership that embraces critical reflection, inclusivity and care. Leadership collectives can support a move in academia from metrics to merits, from a focus on career to care, and enact a shift from disciplinary to inter- and trans-disciplinary research. Academic organisations need to reorient their training programs, work ethics and reward systems to encourage collective excellence and to allow space for future leaders to develop and enact a radically re-imagined vision of how to lead as a collective with care for people and the planet.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Global data set for nitrogen and carbon stable isotopes of tunas - Nathalie Bodin; Heidi Pethybridge; Leanne M. Duffy; Anne Lorrain; Valérie Allain; John M. Logan; Frédéric Ménard; Brittany Graham; C. Anela Choy; Christopher J. Somes; Robert J. Olson; Jock W. Young (Ecology, 2021)
Nitrogen and carbon stable isotope data sets are commonly used to assess complex population to ecosystem responses to natural or anthropogenic changes at regional to global spatial scales, and monthly to decadal timescales. Measured in the tissues of consumers, nitrogen isotopes (δ 15 N) are primarily used to estimate trophic position while carbon isotopes (δ 13 C) describe habitat associations and feeding pathways. Models of both δ 15 N and δ 13 C values and their associated variance can be used to estimate likely dietary contributions and niche width and provide inferences about consumer movement and migration. Stable isotope data have added utility when used in combination with other empirical data sets (e.g., stomach content, movement tracking, bioregionalization, contaminant, or fisheries data) and are increasingly relied upon in food web and ecosystem models. While numerous regional studies publish tables of mean δ 15 N and δ 13 C values, limited individual records have been made available for wider use. Such a deficiency has impeded full utility of the data, which otherwise would facilitate identification of macroscale patterns. The data provided here consist of 4,498 records of individuals of three tuna species, Thunnus alalunga , T. obesus , and T. albacares sampled from all major ocean basins from 2000 to 2015. For each individual tuna, we provide a record of the following: species name, sampling date, sampling location, tuna length, muscle bulk and baseline corrected δ 15 N values, and muscle bulk and, where available, lipid corrected δ 13 C values. We provide these individual records to support comparative studies and more robust modeling projects seeking to improve understanding of complex marine ecosystem dynamics and their responses to a changing environment. There are no copyright restrictions for research and/or teaching purposes. Users are requested to acknowledge their use of the data in publications, research proposals, websites, and other outlets following the citation instructions in Class III, Section B.

Geomechanical characterisation of organic-rich calcareous shale using AFM and nanoindentation - S. P. Graham; M. Rouainia; A. C. Aplin; P. Cubillas; T. D. Fender; P. J. Armitage (Rock Mechanics and Rock Engineering, 2021)
The geomechanical integrity of shale overburden is a highly significant geological risk factor for a range of engineering and energy-related applications including CO $$_2$$ 2 storage and unconventional hydrocarbon production. This paper aims to provide a comprehensive set of high-quality nano- and micro-mechanical data on shale samples to better constrain the macroscopic mechanical properties that result from the microstructural constituents of shale. We present the first study of the mechanical responses of a calcareous shale over length scales of 10 nm to 100 $$\upmu$$ μ m, combining approaches involving atomic force microscopy (AFM), and both low-load and high-load nanoindentation. PeakForce quantitative nanomechanical mapping AFM (PF-QNM) and quantitative imaging (QI-AFM) give similar results for Young’s modulus up to 25 GPa, with both techniques generating values for organic matter of 5–10 GPa. Of the two AFM techniques, only PF-QNM generates robust results at higher moduli, giving similar results to low-load nanoindentation up to 60 GPa. Measured moduli for clay, calcite, and quartz-feldspar are $$22 ± 2\,\hbox { GPa}$$ 22 ± 2 GPa , $$42 ± 8\,\hbox { GPa}$$ 42 ± 8 GPa , and $$55 ± 10\,\hbox { GPa}$$ 55 ± 10 GPa respectively. For calcite and quartz-feldspar, these values are significantly lower than measurements made on highly crystalline phases. High-load nanoindentation generates an unimodal mechanical response in the range of 40–50 GPa for both samples studied here, consistent with calcite being the dominant mineral phase. Voigt and Reuss bounds calculated from low-load nanoindentation results for individual phases generate the expected composite value measured by high-load nanoindentation at length scales of 100–600 $$\upmu$$ μ m. In contrast, moduli measured on more highly crystalline mineral phases using data from literature do not match the composite value. More emphasis should, therefore, be placed on the use of nano- and micro-scale data as the inputs to effective medium models and homogenisation schemes to predict the bulk shale mechanical response.

Corrigendum: Shorebirds Affect Ecosystem Functioning on an Intertidal Mudflat - James M. Booty; Graham J. C. Underwood; Amie Parris; Richard G. Davies; Trevor J. Tolhurst (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Shorebirds Affect Ecosystem Functioning on an Intertidal Mudflat - James M. Booty; Graham J. C. Underwood; Amie Parris; Richard G. Davies; Trevor J. Tolhurst (Frontiers in Marine Science, 2020)
Ecosystem functioning and services have provided a rationale for conservation over the past decades. Intertidal muddy sediments, and the microphytobenthic biofilms that inhabit them, perform crucial ecosystem functions including erosion protection, nutrient cycling and carbon sequestration. It has been suggested that predation on sediment macrofauna by shorebirds may impact biofilms, and shorebirds are known to consume biofilm, potentially causing significant top-down effects on mudflat ecosystem functioning. We carried out an exclusion experiment on the Colne Estuary, Essex, to examine whether shorebird presence significantly affects sediment erodibility measured with a Cohesive Strength Meter (CSM) and microphytobenthos biomass measured using PAM fluorescence (F o ) and chlorophyll a content. We also tested for treatment effects on sediment-water nutrient fluxes [nitrate, nitrite, ammonia, phosphate and dissolved organic carbon (DOC)] during periods of both dark and light incubation. Excluding shorebirds caused statistically significant changes in regulating and provisioning ecosystem functions, including mudflat erodibility and nutrient fluxes. The presence of shorebirds lowered the sediment critical erosion threshold τ cr , reduced nitrate fluxes into the sediment under illumination, lowered nitrate efflux, and reduced phosphate uptake, compared to sediments where birds were excluded. There were no significant differences in macrofauna community composition within the sediment between treatments after 45 days of bird exclusion, suggesting a direct link between shorebird presence or absence and the significant differences in biofilm-related variables. This study introduces previously unknown effects of shorebird presence on ecosystem functions within this system and highlights an area of shorebird science that could aid joint conservation and human provisioning action.

Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis - Nicole M. Foley; Eric J. Petit; Thomas Brazier; John A. Finarelli; Graham M. Hughes; Frédéric Touzalin; Sébastien J. Puechmaille; Emma C. Teeling (Molecular Ecology, 2020)
Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2 = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats.

Horizon scanning for South African biodiversity: A need for social engagement as well as science - Colleen L. Seymour; Lindsey Gillson; Matthew F. Child; Krystal A. Tolley; Jock C. Curie; Jessica M. da Silva; Graham J. Alexander; Pippin Anderson; Colleen T. Downs; Benis N. Egoh; David A. Ehlers Smith; Yvette C. Ehlers Smith; et al. (Ambio, 2020)

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Mitochondrial ROS and Aging: Understanding Exercise as a Preventive Tool - Henver S. Brunetta; Andrew M. Holwerda; Luc J. C. van Loon; Graham P. Holloway (Journal of Science in Sport and Exercise, 2020)

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities - Anne Lorrain; Heidi Pethybridge; Nicolas Cassar; Aurore Receveur; Valérie Allain; Nathalie Bodin; Laurent Bopp; C. Anela Choy; Leanne Duffy; Brian Fry; Nicolas Goñi; Brittany S. Graham; et al. (Global Change Biology, 2020)
Considerable uncertainty remains over how increasing atmospheric CO 2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ 13 C values of 0.8‰–2.5‰ were observed across three tuna species sampled globally, with more substantial changes in the Pacific Ocean compared to the Atlantic and Indian Oceans. Tuna recorded not only the Suess effect, that is, fossil fuel‐derived and isotopically light carbon being incorporated into marine ecosystems, but also recorded profound changes at the base of marine food webs. We suggest a global shift in phytoplankton community structure, for example, a reduction in 13 C‐rich phytoplankton such as diatoms, and/or a change in phytoplankton physiology during this period, although this does not rule out other concomitant changes at higher levels in the food webs. Our study establishes tuna δ 13 C values as a candidate essential ocean variable to assess complex ecosystem responses to climate change at regional to global scales and over decadal timescales. Finally, this time series will be invaluable in calibrating and validating global earth system models to project changes in marine biota.

Body size and dietary risk factors for aggressive prostate cancer: a case–control study - Mikaela Pal; Allison M. Hodge; Nathan Papa; Robert J. MacInnis; Julie K. Bassett; Damien Bolton; Ian D. Davis; Jeremy Millar; Dallas R. English; John L. Hopper; Gianluca Severi; Melissa C. Southey; et al. (Cancer Causes & Control, 2019)

Managing Marine Protected Areas in Remote Areas: The Case of the Subantarctic Heard and McDonald Islands - Cassandra M. Brooks; Graham Epstein; Natalie C. Ban (Frontiers in Marine Science, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Drill-Specific Head Impacts in Collegiate Football Practice: Implications for Reducing “Friendly Fire” Exposure - Breton M. Asken; Zechariah S. Brooke; Taylor C. Stevens; Paul G. Silvestri; Matthew J. Graham; Michael S. Jaffee; James R. Clugston (Annals of Biomedical Engineering, 2019)

Chronic stress from fishing gear entanglement is recorded in baleen from a bowhead whale ( Balaena mysticetus ) - Rosalind M. Rolland; Katherine M. Graham; Raphaela Stimmelmayr; Robert S. Suydam; John C. George (Marine Mammal Science, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Growth rates of Porites astreoides and Orbicella franksi in mesophotic habitats surrounding St. Thomas, US Virgin Islands - Sarah H. Groves; Daniel M. Holstein; Ian C. Enochs; Graham Kolodzeij; Derek P. Manzello; Marilyn E. Brandt; Tyler B. Smith (Coral Reefs, 2018)

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Environmental variation is a major predictor of global trait turnover in mammals - Ben G. Holt; Gabriel C. Costa; Caterina Penone; Jean‐Philippe Lessard; Thomas M. Brooks; Ana D. Davidson; S. Blair Hedges; Volker C. Radeloff; Carsten Rahbek; Carlo Rondinini; Catherine H. Graham (Journal of Biogeography, 2018)
Aim To evaluate how environment and evolutionary history interact to influence global patterns of mammal trait diversity (a combination of 14 morphological and life‐history traits). Location The global terrestrial environment. Taxon Terrestrial mammals. Methods We calculated patterns of spatial turnover for mammalian traits and phylogenetic lineages using the mean nearest taxon distance. We then used a variance partitioning approach to establish the relative contribution of trait conservatism, ecological adaptation and clade specific ecological preferences on global trait turnover. Results We provide a global scale analysis of trait turnover across mammalian terrestrial assemblages, which demonstrates that phylogenetic turnover by itself does not predict trait turnover better than random expectations. Conversely, trait turnover is consistently more strongly associated with environmental variation than predicted by our null models. The influence of clade‐specific ecological preferences, reflected by the shared component of phylogenetic turnover and environmental variation, was considerably higher than expectations. Although global patterns of trait turnover are dependent on the trait under consideration, there is a consistent association between trait turnover and environmental predictive variables, regardless of the trait considered. Main conclusions Our results suggest that changes in phylogenetic composition are not always coupled with changes in trait composition on a global scale and that environmental conditions are strongly associated with patterns of trait composition across species assemblages, both within and across phylogenetic clades.

The missing half of the subduction factory: shipboard results from the Izu rear arc, IODP Expedition 350 - Cathy J. Busby; Yoshihiko Tamura; Peter Blum; Gilles Guèrin; Graham D. M. Andrews; Abigail K. Barker; Julien L. R. Berger; Everton M. Bongiolo; Manuela Bordiga; Susan M. DeBari; James B. Gill; Cedric Hamelin; et al. (International Geology Review, 2017)

The signature of human pressure history on the biogeography of body mass in tetrapods - Giovanni Rapacciuolo; Julie Marin; Gabriel C. Costa; Matthew R. Helmus; Jocelyn E. Behm; Thomas M. Brooks; S. Blair Hedges; Volker C. Radeloff; Bruce E. Young; Catherine H. Graham (Global Ecology and Biogeography, 2017)
Aim Examining the biogeography of body size is crucial for understanding how animal communities are assembled and maintained. In tetrapods, body size varies predictably with temperature, moisture, productivity seasonality and topographical complexity. Although millennial‐scale human pressures are known to have led to the extinction of primarily large‐bodied tetrapods, human pressure history is often ignored in studies of body size that focus on extant species. Here, we analyse 11,377 tetrapod species of the Western Hemisphere to test whether millennial‐scale human pressures have left an imprint on contemporary body mass distributions throughout the tetrapod clade. Location Western Hemisphere. Time period Contemporary. Major taxa studied Tetrapods (birds, mammals, amphibians and reptiles). Methods We mapped the distribution of assemblage‐level median tetrapod body mass at a resolution of 110 km across the Western Hemisphere. We then generated multivariate models of median body mass as a function of temperature, moisture, productivity seasonality and topographical complexity, as well as two variables capturing the history of human population density and human‐induced land conversion over the past 12,000 years. We controlled for both spatial and phylogenetic autocorrelation effects on body mass–environment relationships. Results Human pressures explain a small but significant portion of geographical variation in median body mass that cannot be explained by ecological constraints alone. Overall, the median body mass of tetrapod assemblages is lower than expected in areas with a longer history of high human population density and land conversion, but there are important differences among tetrapod classes. Main conclusions At this broad scale, the effect of human pressure history on tetrapod body mass is low relative to that of ecology. However, ignoring spatial variation in the history of human pressure is likely to lead to bias in studies of the present‐day functional composition of tetrapod assemblages, at least in areas that have long been influenced by humans.

Physiological proteins in resource-limited herbivores experiencing a population die-off - R. Garnier; A. I. Bento; C. Hansen; J. G. Pilkington; J. M. Pemberton; A. L Graham (The Science of Nature, 2017)

A dosing algorithm for metformin based on the relationships between exposure and renal clearance of metformin in patients with varying degrees of kidney function - Janna K. Duong; M. Y. A. M. Kroonen; S. S. Kumar; H. L. Heerspink; C. M. Kirkpatrick; G. G. Graham; K. M. Williams; R. O. Day (European Journal of Clinical Pharmacology, 2017)

New perspectives on the regulation of iron absorption via cellular zinc concentrations in humans - Marija Knez; Robin D. Graham; Ross M. Welch; James C. R. Stangoulis (Critical Reviews in Food Science and Nutrition, 2017)

Multi-criteria correlation of tephra deposits to source centres applied in the Auckland Volcanic Field, New Zealand - Jenni L. Hopkins; Colin J. N. Wilson; Marc-Alban Millet; Graham S. Leonard; Christian Timm; Lucy E. McGee; Ian E. M. Smith; Euan G. C. Smith (Bulletin of Volcanology, 2017)

Bradyrhizobium centrolobii and Bradyrhizobium macuxiense sp. nov. isolated from Centrolobium paraense grown in soil of Amazonia, Brazil - Daniele C. Michel; Samuel R. Passos; Jean L. Simões-Araujo; Alexandre C. Baraúna; Krisle da Silva; Marcia M. Parma; Itamar S. Melo; Sofie E. De Meyer; Graham O’Hara; Jerri E. Zilli (Archives of Microbiology, 2017)

White-chinned petrel population estimate, Disappointment Island (Auckland Islands) - Kalinka Rexer-Huber; Graham C. Parker; Paul M. Sagar; David R. Thompson (Polar Biology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Soil compartment is a major determinant of the impact of simulated rainfall on desert microbiota - Shazia N. Aslam; Alex J. Dumbrell; Jamal S. Sabir; Mohammed H. Z. Mutwakil; Mohammed M. N. Baeshen; Salah E. M. Abo‐Aba; Dave R. Clark; Steven A. Yates; Nabih A. Baeshen; Graham J. C. Underwood; Terry J. McGenity (Environmental Microbiology, 2016)
Summary Although desert soils support functionally important microbial communities that affect plant growth and influence many biogeochemical processes, the impact of future changes in precipitation patterns on the microbiota and their activities is largely unknown. We performed in‐situ experiments to investigate the effect of simulated rainfall on bacterial communities associated with the widespread perennial shrub, Rhazya stricta in Arabian desert soils. The bacterial community composition was distinct between three different soil compartments: surface biological crust, root‐attached, and the broader rhizosphere. Simulated rainfall had no significant effect on the overall bacterial community composition, but some population‐level responses were observed, especially in soil crusts where Betaproteobacteria, Sphingobacteria, and Bacilli became more abundant. Bacterial biomass in the nutrient‐rich crust increased three‐fold one week after watering, whereas it did not change in the rhizosphere, despite its much higher water retention. These findings indicate that between rainfall events, desert‐soil microbial communities enter into stasis, with limited species turnover, and reactivate rapidly and relatively uniformly when water becomes available. However, microbiota in the crust, which was relatively enriched in nutrients and organic matter, were primarily water‐limited, compared with the rhizosphere microbiota that were co‐limited by nutrients and water.

Species and functional diversity accumulate differently in mammals - Brunno F. Oliveira; Antonin Machac; Gabriel C. Costa; Thomas M. Brooks; Ana D. Davidson; Carlo Rondinini; Catherine H. Graham (Global Ecology and Biogeography, 2016)
Aim Whether the gradients of global diversity conform to equilibrium or non‐equilibrium dynamics remains an unresolved question in ecology and evolution. Here, we evaluate four prominent hypotheses which invoke either equilibrium (more individuals, niche diversity) or non‐equilibrium dynamics (diversification rate, evolutionary time) to explain species richness and functional diversity of mammals worldwide. Location Global. Methods We combine structural equation modelling with simulations to examine whether species richness and functional diversity are in equilibrium with environmental conditions (climate, productivity) or whether they vary with non‐equilibrium factors (diversification rates, evolutionary time). We use the newest and most inclusive phylogenetic, distributional and trait data for mammals. Results We find that species richness and functional diversity are decoupled across multiple regions of the world. While species richness correlates closely with environmental conditions, functional diversity depends mostly on non‐equilibrium factors (evolutionary time to overcome niche conservatism). Moreover, functional diversity plateaus with species richness, such that species‐rich regions (especially the Neotropics) host many species that are apparently functionally redundant. Main conclusions We conclude that species richness depends on environmental factors while functional diversity depends on the evolutionary history of the region. Our work further challenges the classic notion that highly productive regions host more species because they offer a great diversity of ecological niches. Instead, they suggest that productive regions offer more resources, which allow more individuals, populations and species to coexist within a region, even when the species are apparently functionally redundant (the more individuals hypothesis). Together these findings demonstrate how ecological (the total amount of resources) and evolutionary factors (time to overcome niche conservatism) might have interacted to generate the striking diversity of mammals and their life histories.

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Does participatory forest management program lead to efficient forest resource use and improved rural livelihoods? Experiences from Mua-Livulezi Forest Reserve, Malawi - T. C. Senganimalunje; P. W. Chirwa; F. D. Babalola; M. A. Graham (Agroforestry Systems, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Global and European climate impacts of a slowdown of the AMOC in a high resolution GCM - L. C. Jackson; R. Kahana; T. Graham; M. A. Ringer; T. Woollings; J. V. Mecking; R. A. Wood (Climate Dynamics, 2015)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Adolescent dietary vitamin D and sun exposure in relation to benign breast disease - Caroline E. Boeke; Rulla M. Tamimi; Catherine S. Berkey; Graham A. Colditz; Edward Giovannucci; Susan Malspeis; Walter C. Willett; A. Lindsay Frazier (Cancer Causes & Control, 2015)

The “nutrient pump:” Iron‐poor sediments fuel low nitrogen‐to‐phosphorus ratios and cyanobacterial blooms in polymictic lakes - Diane M. Orihel; David W. Schindler; Nathaniel C. Ballard; Mark D. Graham; David W. O'Connell; Lindsey R. Wilson; Rolf D. Vinebrooke (Limnology and Oceanography, 2015)
Several lines of evidence from a eutrophic lake show how polymixis enables phosphorus (P) released from anoxic, iron (Fe)‐poor sediments to lower nitrogen‐to‐phosphorus (N : P) ratios and stimulate cyanobacterial blooms. Detailed sediment analyses revealed extensive formation of Fe sulfides, which suppressed porewater Fe levels and prevented sequestration of P in Fe minerals. Experimental additions of Fe significantly decreased the flux of dissolved P from warm, anoxic sediments, increasing N : P ratios in porewater and overlying water. The net midsummer effect of polymixis and P release from Fe‐poor sediments quickly doubled the total P in the euphotic zone during a period of very low external P loading. This internal “nutrient pump” decreased N : P in surface waters and led to a cyanobacterial bloom comprised primarily of diazotrophic Anabaena and Aphanizomenon spp. along with nonheterocystous and potentially toxic Microcystis icthyoblabe and Woronichinia naegelianum . Concentrations of the cyanotoxin, microcystin, in this lake were typically elevated during, or shortly after, episodes of internal P loading. Our study demonstrates an important mechanism underlying the increasing cyanobacterial dominance of weakly stratified eutrophic north temperate lakes, and warns of further increases under a warming climate.

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Setting the stage for a global-scale trophic analysis of marine top predators: a multi-workshop review - J. W. Young; R. J. Olson; F. Ménard; P. M. Kuhnert; L. M. Duffy; V. Allain; J. M. Logan; A. Lorrain; C. J. Somes; B. Graham; N. Goñi; H. Pethybridge; et al. (Reviews in Fish Biology and Fisheries, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Color, Yield, and Texture of Heat and High Pressure Processed Mussels During Ice Storage - Sravani Gupta; Mohammed M. Farid; Graham C. Fletcher; Laurence D. Melton (Journal of Aquatic Food Product Technology, 2015)

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

Understanding the spectacular failure of DNA barcoding in willows ( Salix ): Does this result from a trans‐specific selective sweep? - Diana M. Percy; George W. Argus; Quentin C. Cronk; Aron J. Fazekas; Prasad R. Kesanakurti; Kevin S. Burgess; Brian C. Husband; Steven G. Newmaster; Spencer C.H. Barrett; Sean W. Graham (Molecular Ecology, 2014)
Willows ( Salix : Salicaceae) form a major ecological component of Holarctic floras and consequently are an obvious target for a DNA ‐based identification system. We surveyed two to seven plastid genome regions (~3.8 kb; ~3% of the genome) from 71 Salix species across all five subgenera, to assess their performance as DNA barcode markers. Although Salix has a relatively high level of interspecific hybridization, this may not sufficiently explain the near complete failure of barcoding that we observed: only one species had a unique barcode. We recovered 39 unique haplotypes, from more than 500 specimens, that could be partitioned into six major haplotype groups. A unique variant of group I (haplotype 1*) was shared by 53 species in three of five Salix subgenera. This unusual pattern of haplotype sharing across infrageneric taxa is suggestive of either a massive nonrandom coalescence failure (incomplete lineage sorting), or of repeated plastid capture events, possibly including a historical selective sweep of haplotype 1* across taxonomic sections. The former is unlikely as molecular dating indicates that haplotype 1* originated recently and is nested in the oldest major haplotype group in the genus. Further, we detected significant non‐neutrality in the frequency spectrum of mutations in group I, but not outside group I, and demonstrated a striking absence of geographical (isolation by distance) effects in the haplotype distributions of this group. The most likely explanation for the patterns we observed involves recent repeated plastid capture events, aided by widespread hybridization and long‐range seed dispersal, but primarily propelled by one or more trans‐species selective sweeps.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Combined effects of flow condition and parasitism on shoaling behaviour of female guppies Poecilia reticulata - F. A. Hockley; C. A. M. E. Wilson; N. Graham; J. Cable (Behavioral Ecology and Sociobiology, 2014)

Towards improving the accuracy of opium yield estimates with remote sensing - Toby W. Waine; Daniel M. Simms; John C. Taylor; Graham R. Juniper (International Journal of Remote Sensing, 2014)

The application of time-series MODIS NDVI profiles for the acquisition of crop information across Afghanistan - Daniel M. Simms; Toby W. Waine; John C. Taylor; Graham R. Juniper (International Journal of Remote Sensing, 2014)

Tissue Engineering and Regenerative Repair in Wound Healing - Michael S. Hu; Zeshaan N. Maan; Jen-Chieh Wu; Robert C. Rennert; Wan Xing Hong; Tiffany S. Lai; Alexander T. M. Cheung; Graham G. Walmsley; Michael T. Chung; Adrian McArdle; Michael T. Longaker; H. Peter Lorenz (Annals of Biomedical Engineering, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Relating microfeatures of soil organic matter to C stabilisation: optical microscopy, SEM-EDS, abiotic oxidation - G. Falsone; C. A. Wilson; J. M. Cloy; M. C. Graham; E. Bonifacio (Biology and Fertility of Soils, 2014)

Groundwater residence time in a dissected and weathered sandstone plateau: Kulnura–Mangrove Mountain aquifer, NSW, Australia - D. I. Cendón; S. I. Hankin; J. P. Williams; M. Van der Ley; M. Peterson; C. E. Hughes; K. Meredith; I. T. Graham; S. E. Hollins; V. Levchenko; R. Chisari (Australian Journal of Earth Sciences, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Brain fingerprinting field studies comparing P300-MERMER and P300 brainwave responses in the detection of concealed information - Lawrence A. Farwell; Drew C. Richardson; Graham M. Richardson (Cognitive Neurodynamics, 2013)

Erratum to: Demography and movement patterns of leopard sharks (Triakis semifasciata ) aggregating near the head of a submarine canyon along the open coast of southern California, USA - A. P. Nosal; D. C. Cartamil; J. W. Long; M. Lührmann; N. C. Wegner; J. B. Graham (Environmental Biology of Fishes, 2013)

Demography and movement patterns of leopard sharks (Triakis semifasciata) aggregating near the head of a submarine canyon along the open coast of southern California, USA - A. P. Nosal; D. C. Cartamil; J. W. Long; M. Lührmann; N. C. Wegner; J. B. Graham (Environmental Biology of Fishes, 2013)

Evidence for distinct stages of magma history recorded by the compositions of accessory apatite and zircon - A. J. Miles; C. M. Graham; C. J. Hawkesworth; M. R. Gillespie; R. W. Hinton (Contributions to Mineralogy and Petrology, 2013)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Diatom-inferred late Pleistocene and Holocene palaeolimnological changes in the Ioannina basin, northwest Greece - Timothy D. Jones; Ian T. Lawson; Jane M. Reed; Graham P. Wilson; Melanie J. Leng; Merle Gierga; Stefano M. Bernasconi; Rienk H. Smittenberg; Irka Hajdas; Charlotte L. Bryant; P. C. Tzedakis (Journal of Paleolimnology, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

A unified model for gold mineralisation in accretionary orogens and implications for regional-scale exploration targeting methods - Jon M. A. Hronsky; David I. Groves; Robert R. Loucks; Graham C. Begg (Mineralium Deposita, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Episodic heterogeneous decline and recovery of coral cover in the Indian Ocean - M. Ateweberhan; T. R. McClanahan; N. A. J. Graham; C. R. C. Sheppard (Coral Reefs, 2011)

Support for global climate reorganization during the “Medieval Climate Anomaly” - N. E. Graham; C. M. Ammann; D. Fleitmann; K. M. Cobb; J. Luterbacher (Climate Dynamics, 2011)

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

Towards an understanding of the nature of resistance to Phytophthora root rot in red raspberry - J. Graham; C. A. Hackett; K. Smith; M. Woodhead; K. MacKenzie; I. Tierney; D. Cooke; M. Bayer; N. Jennings (Theoretical and Applied Genetics, 2011)

Spatiotemporal patterns of marine mammal distribution in coastal waters of Galicia, NW Spain - Evangelos Spyrakos; Tania C. Santos-Diniz; Gema Martinez-Iglesias; Jesus M. Torres-Palenzuela; Graham J. Pierce (Hydrobiologia, 2011)

Extinction vulnerability of coral reef fishes - Nicholas A. J. Graham; Pascale Chabanet; Richard D. Evans; Simon Jennings; Yves Letourneur; M. Aaron MacNeil; Tim R. McClanahan; Marcus C. Öhman; Nicholas V. C. Polunin; Shaun K. Wilson (Ecology Letters, 2011)

Spatial patterns of plant diversity below‐ground as revealed by DNA barcoding - PRASAD R. KESANAKURTI; ARON J. FAZEKAS; KEVIN S. BURGESS; DIANA M. PERCY; STEVEN G. NEWMASTER; SEAN W. GRAHAM; SPENCER C. H. BARRETT; MEHRDAD HAJIBABAEI; BRIAN C. HUSBAND (Molecular Ecology, 2011)
Our understanding of the spatial organization of root diversity in plant communities and of the mechanisms of community assembly has been limited by our ability to identify plants based on root tissue, especially in diverse communities. Here, we test the effectiveness of the plastid gene rbcL , a core plant DNA barcoding marker, for investigating spatial patterns of root diversity, and relate observed patterns to above‐ground community structure. We collected 3800 root fragments from four randomly positioned, 1‐m‐deep soil profiles (two vertical transects per plot), located in an old‐field community in southern Ontario, Canada, and extracted and sequenced DNA from 1531 subsampled fragments. We identified species by comparing sequences with a DNA barcode reference library developed previously for the local flora. Nearly 85% of sampled root fragments were successfully sequenced and identified as belonging to 29 plant species or species groups. Root abundance and species richness varied in horizontal space and were negatively correlated with soil depth. The relative abundance of taxa below‐ground was correlated with their frequency above‐ground ( r = 0.73, P = 0.0001), but several species detected in root tissue were not observed in above‐ground quadrats. Multivariate analyses indicated that diversity was highly structured below‐ground, and associated with depth, root morphology, soil chemistry and soil texture, whereas little structure was evident above‐ground. Furthermore, analyses of species co‐occurrence indicates strong species segregation overall but random co‐occurrence among confamilials. Our results provide insights into the role of environmental filtering and competitive interactions in the organization of plant diversity below‐ground, and also demonstrate the utility of barcoding for the identification of plant roots.

Patterns of crop-raiding by elephants, Loxodonta africana , in Laikipia, Kenya, and the management of human–elephant conflict - MAXIMILIAN D. GRAHAM; BENEDIKT NOTTER; WILLIAM M. ADAMS; PHYLLIS C. LEE; TOBIAS NYUMBA OCHIENG (Systematics and Biodiversity, 2010)

Are infestations of Cymo melanodactylus killing Acropora cytherea in the Chagos archipelago? - M. S. Pratchett; N. A. J. Graham; C. R. C. Sheppard; B. Mayes (Coral Reefs, 2010)

Lack of evidence for vertical transmission of SAV 3 using gametes of Atlantic salmon, Salmo salar L., exposed by natural and experimental routes - R T Kongtorp; A Stene; P A Andreassen; V Aspehaug; D A Graham; T M Lyngstad; A B Olsen; R S Olsen; M Sandberg; N Santi; C Wallace; O Breck (Journal of Fish Diseases, 2010)
Pancreas disease (PD) is an important cause of losses in farmed salmonids in Norway, the United Kingdom and Ireland. As the spread of salmonid alphavirus (SAV), the causal agent, to naïve populations is of major concern to the farming industry, it is important to uncover the transmission routes of the virus. This study was conducted to investigate the potential for vertical transmission of SAV subtype 3. Progeny of broodstock with signs of late‐stage PD and persistent RT‐PCR signals for SAV were followed from fertilization to smoltification in an experimental facility. Fertilized ova were either not disinfected or taken through one of three different disinfection regimes. Also, ova and milt from uninfected broodfish from a different population were exposed to a cell‐cultured strain of SAV 3 immediately before fertilization to simulate a viraemic phase in parent fish. A group of uninfected controls were also included in the study. Fertilized ova from bath exposed and negative control groups were double disinfected. Following fertilization, experimental fish went through a normal freshwater phase. However, fry were stressed at first feeding to enhance replication of possibly latent virus. Smoltification was induced by an artificial light regime, and experimental fish were followed to the late smoltification phase. Selected samples were investigated by real‐time RT‐PCR for SAV, by histology for evidence of PD and by serology for neutralising antibodies against SAV. All analysed samples of progeny were negative. This result shows that SAV 3 is not readily transmitted vertically from parents to offspring. Additional negative PCR results from salmon sampled in commercial hatcheries support these findings. Also, recent studies have shown that risk factors for the horizontal transmission route explain the vast majority of PD outbreaks in Norway. It is concluded that if it happens at all, vertical transmission is of minor importance in the spread of SAV 3.

Public Internet‐connected cameras used as a cross‐continental ground‐based plant phenology monitoring system - ERIC A. GRAHAM; ERIN C. RIORDAN; ERIC M. YUEN; DEBORAH ESTRIN; PHILIP W. RUNDEL (Global Change Biology, 2010)
Plant phenology is highly sensitive to changes in environmental conditions and can vary widely across landscapes. Current observation methods are either manual for small‐scale, high precision measurements or by satellite remote sensing for large‐scale, low spatial resolution measurement. The development of inexpensive approaches is necessary to advance large scale, high precision phenology monitoring. The use of publicly available, Internet‐connected cameras, often associated with airports, national parks, and roadway conditions, for detecting and monitoring plant phenology at a continental scale can augment existing ground and satellite‐based methodologies. We collected twice‐daily images from over 1100 georeferenced public cameras across North America from February 2008 to 2009. Using a test subset of these cameras, we compared modeled spring ‘green‐up’ with that from co‐occurring remote sensing products. Although varying image exposure and color correction introduced noise to camera measurements, we were able to correlate spring green‐up across North America with visual validation from images and detect a latitudinal trend. Public cameras had an equivalent or higher ability to detect spring compared with satellite‐based data for corresponding locations, with fewer numbers of poor quality days, shorter continuous bad data days, and significantly lower errors of spring estimates. Manual image segmentation into deciduous, evergreen, and understory vegetation allowed detection of spring and fall onset for multiple vegetation types. Additional advantages of a public camera‐based monitoring system include frequent image capture (subdaily) and the potential to detect quantitative responses to environmental changes in organisms, species, and communities. Public cameras represent a relatively untapped and freely available resource for supporting large‐scale ecological and environmental monitoring.

Trophic status of Chlamydomonas reinhardtii influences the impact of iron deficiency on photosynthesis - Aimee M. Terauchi; Graham Peers; Marilyn C. Kobayashi; Krishna K. Niyogi; Sabeeha S. Merchant (Photosynthesis Research, 2010)

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)

A Water Accounting System for Strategic Water Management - Graham M. Turner; Timothy M. Baynes; Bertram C. McInnis (Water Resources Management, 2010)

Population genetic structure of the Daubenton’s bat (Myotis daubentonii) in western Europe and the associated occurrence of rabies - Helen Atterby; James N. Aegerter; Graham C. Smith; Christine M. Conyers; Theodore R. Allnutt; Manuel Ruedi; Alan D. MacNicoll (European Journal of Wildlife Research, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Coral mortality versus structural collapse as drivers of corallivorous butterflyfish decline - N. A. J. Graham; S. K. Wilson; M. S. Pratchett; N. V. C. Polunin; M. D. Spalding (Biodiversity and Conservation, 2009)

A prevalence screen of MRSA nasal colonisation amongst UK doctors in a non-clinical environment - R. R. W. Brady; C. McDermott; C. Graham; E. M. Harrison; G. Eunson; A. P. Fraise; M. G. Dunlop; A. P. Gibb (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effect of anti-fibrinolytic therapy on experimental melanoma metastasis - Jennifer M. Kirstein; Kevin C. Graham; Lisa T. MacKenzie; Danielle E. Johnston; Leslie J. Martin; Alan B. Tuck; Ian C. MacDonald; Ann F. Chambers (Clinical & Experimental Metastasis, 2009)

Hierarchical drivers of reef‐fish metacommunity structure - M. Aaron MacNeil; Nicholas A. J. Graham; Nicholas V. C. Polunin; Michel Kulbicki; René Galzin; Mireille Harmelin-Vivien; Steven P. Rushton (Ecology, 2009)
Coral reefs are highly complex ecological systems, where multiple processes interact across scales in space and time to create assemblages of exceptionally high biodiversity. Despite the increasing frequency of hierarchically structured sampling programs used in coral‐reef science, little progress has been made in quantifying the relative importance of processes operating across multiple scales. The vast majority of reef studies are conducted, or at least analyzed, at a single spatial scale, ignoring the implicitly hierarchical structure of the overall system in favor of small‐scale experiments or large‐scale observations. Here we demonstrate how α (mean local number of species), β diversity (degree of species dissimilarity among local sites), and γ diversity (overall species richness) vary with spatial scale, and using a hierarchical, information‐theoretic approach, we evaluate the relative importance of site‐, reef‐, and atoll‐level processes driving the fish metacommunity structure among 10 atolls in French Polynesia. Process‐based models, representing well‐established hypotheses about drivers of reef‐fish community structure, were assembled into a candidate set of 12 hierarchical linear models. Variation in fish abundance, biomass, and species richness were unevenly distributed among transect, reef, and atoll levels, establishing the relative contribution of variation at these spatial scales to the structure of the metacommunity. Reef‐fish biomass, species richness, and the abundance of most functional‐groups corresponded primarily with transect‐level habitat diversity and atoll‐lagoon size, whereas detritivore and grazer abundances were largely correlated with potential covariates of larval dispersal. Our findings show that (1) within‐transect and among‐atoll factors primarily drive the relationship between α and γ diversity in this reef‐fish metacommunity; (2) habitat is the primary correlate with reef‐fish metacommunity structure at multiple spatial scales; and (3) inter‐atoll connectedness was poorly correlated with the nonrandom clustering of reef‐fish species. These results demonstrate the importance of modeling hierarchical data and processes in understanding reef‐fish metacommunity structure.

Species effects on ecosystem processes are modified by faunal responses to habitat composition - Mark T. Bulling; Martin Solan; Kirstie E. Dyson; Gema Hernandez-Milian; Patricia Luque; Graham J. Pierce; Dave Raffaelli; David M. Paterson; Piran C. L. White (Oecologia, 2008)

Exploitation and habitat degradation as agents of change within coral reef fish communities - S. K. WILSON; R. FISHER; M. S. PRATCHETT; N. A. J. GRAHAM; N. K. DULVY; R. A. TURNER; A. CAKACAKA; N. V. C. POLUNIN; S. P. RUSHTON (Global Change Biology, 2008)
Over‐exploitation and habitat degradation are the two major drivers of global environmental change and are responsible for local extinctions and declining ecosystem services. Here we compare the top‐down effect of exploitation by fishing with the bottom‐up influence of habitat loss on fish communities in the most diverse of ecological systems, coral reefs. Using a combination of multivariate techniques and path analyses, we illustrate that the relative importance of coral cover and fishing in controlling fish abundance on remote Fijian reefs varies between species and functional groups. A decline in branching Acropora coral is strongly associated with a decline in abundance of coral‐feeding species, and a decrease in coral‐associated habitat complexity, which has indirectly contributed to reduced abundance of small‐bodied damselfish. In contrast, reduced fishing pressure, brought about by declining human populations and a shift to alternate livelihoods, is associated with increased abundance of some piscivores and fisheries target species. However, availability of prey is controlled by coral‐associated habitat complexity and appears to be a more important driver of total piscivore abundance compared with fishing pressure. Effects of both fishing and coral loss are stronger on individual species than functional groups, as variation in the relative importance of fishing or coral loss among species within the same functional group attenuated the impact of either of these potential drivers at the functional level. Overall, fishing continues to have an influence on Fijian fish communities; however, habitat loss is currently the overriding agent of change. The importance of coral loss mediated by climate change is expected to have an increasing contribution to fish community dynamics, particularly in remote locations or where the influence of fishing is waning.

Nile Red Synchronous Scan Fluorescence Spectroscopy to Follow Matrix Modification in Sol–Gel Derived Media and its Effect on the Peroxidase Activity of cytochrome c - Ana Rei; M. Isabel C. Ferreira; Graham Hungerford (Journal of Fluorescence, 2008)

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

Detection heterogeneity in underwater visual‐census data - M. A. MacNeil; N. A. J. Graham; M. J. Conroy; C. J. Fonnesbeck; N. V. C. Polunin; S. P. Rushton; P. Chabanet; T. R. McClanahan (Journal of Fish Biology, 2008)
This study shows how capture–mark–recapture (CMR) models can provide robust estimates of detection heterogeneity (sources of bias) in underwater visual‐census data. Detection biases among observers and fish family groups were consistent between fished and unfished reef sites in Kenya, even when the overall level of detection declined between locations. Species characteristics were the greatest source of detection heterogeneity and large, highly mobile species were found to have lower probabilities of detection than smaller, site‐attached species. Fish family and functional‐group detectability were also found to be lower at fished locations, probably due to differences in local abundance. Because robust CMR models deal explicitly with sampling where not all species are detected, their use is encouraged for studies addressing reef‐fish community dynamics.

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

A review of cephalopod–environment interactions in European Seas - Graham J. Pierce; Vasilis D. Valavanis; Angel Guerra; Patricia Jereb; Lydia Orsi-Relini; Jose M. Bellido; Isidora Katara; Uwe Piatkowski; João Pereira; Eduardo Balguerias; Ignacio Sobrino; Eugenia Lefkaditou; et al. (Hydrobiologia, 2008)

Historical and contemporary evidence of a mutton snapper (Lutjanus analis Cuvier, 1828) spawning aggregation fishery in decline - R. T. Graham; R. Carcamo; K. L. Rhodes; C. M. Roberts; N. Requena (Coral Reefs, 2008)

Is MSH2 a breast cancer susceptibility gene? - EE Ming Wong; Andrea A. Tesoriero; Gulietta M. Pupo; Margaret R. E. McCredie; Graham G. Giles; John L. Hopper; Graham J. Mann; David E. Goldgar; Melissa C. Southey (Familial Cancer, 2008)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Declining reliance on marine resources in remote South Pacific societies: ecological versus socio-economic drivers - R. A. Turner; A. Cakacaka; N. A. J. Graham; N. V. C. Polunin; M. S. Pratchett; S. M. Stead; S. K. Wilson (Coral Reefs, 2007)

Characterisation and partial sequence analysis of two novel cypoviruses isolated from the winter moth Operophtera brumata (Lepidoptera: Geometridae) - Robert I. Graham; Shujing Rao; Steven M. Sait; Peter P. C. Mertens; Rosemary S. Hails; Robert D. Possee (Virus Genes, 2007)

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.

Erratum to: Predictability of coral bleaching from synoptic satellite and in situ temperature observations - T. R. McClanahan; M. Ateweberhan; C. Ruiz Sebastián; N. A. J. Graham; S. K. Wilson; J. H. Bruggemann; M. M. M. Guillaume (Coral Reefs, 2007)

Predictability of coral bleaching from synoptic satellite and in situ temperature observations - T. R. McClanahan; M. Ateweberhan; C. Ruiz Sebastián; N. A. J. Graham; S. K. Wilson; J. H. Bruggemann; M. M. M. Guillaume (Coral Reefs, 2007)

First laboratory confirmation of salmonid alphavirus infection in Italy and Spain - D A Graham; H M Rowley; E Fringuelli; G Bovo; A Manfrin; M F McLoughlin; C Zarza; M Khalili; D Todd (Journal of Fish Diseases, 2007)

Biophysical properties of salmonid alphaviruses: influence of temperature and pH on virus survival - D A Graham; C Staples; C J Wilson; H Jewhurst; K Cherry; A Gordon; H M Rowley (Journal of Fish Diseases, 2007)
A series of laboratory studies were undertaken to investigate the survival of salmonid alphaviruses (SAV) under a range of conditions relevant to waste disposal, persistence and spread in the field, and to laboratory studies and testing. SAV was found to be rapidly inactivated in the presence of high levels of organic matter at 60 °C at pH 7.2 and at pH 4 and pH 12 at 4 °C, suggesting that composting, ensiling and alkaline hydrolysis would all be effective at inactivating virus in fish waste. Testing was conducted under sterile conditions at 4, 10, 15 and 20 °C in sea water, half‐strength sea water and fresh (hard) water, both in the absence and the presence of added organic matter. Virus survival was shown to be inversely related to temperature, and to be reduced by the presence of organic matter. Calculated half lives ( t 1/2 ) under these conditions ranged from 61.0 to 1.5 days. Testing in non‐sterile sea water resulted in reduced t 1/2 values. The half life of SAV in serum was also found to be inversely related to temperature, emphasizing the need for rapid shipment of samples at 4 °C to laboratories for virus isolation studies.

Phase shifts and the role of herbivory in the resilience of coral reefs - M. H. Ledlie; N. A. J. Graham; J. C. Bythell; S. K. Wilson; S. Jennings; N. V. C. Polunin; J. Hardcastle (Coral Reefs, 2007)

Does size matter for dispersal distance? - David G. Jenkins; Camille R. Brescacin; Craig V. Duxbury; Jennifer A. Elliott; Jennafer A. Evans; Katherine R. Grablow; Melissa Hillegass; Boyd N. Lyon; Genevieve A. Metzger; Michelle L. Olandese; Diana Pepe; Greg A. Silvers; et al. (Global Ecology and Biogeography, 2007)
Aim The aim of this study is to answer the questions: (1) do small organisms disperse farther than large, or vice versa; and (2) does the observed pattern differ for passive and active dispersers? These questions are central to several themes in biogeography (including microbial biogeography), macroecology, metacommunity ecology and conservation biology. Location The meta‐analysis was conducted using published data collected worldwide. Methods We collected and analysed 795 data values in the peer‐reviewed literature for direct observations of both maximal dispersal distance and mass of the dispersing organisms (e.g. seeds, not trees). Analysed taxa ranged in size from bacteria to whales. We applied macroecology analyses based on null models (using Monte Carlo randomizations) to test patterns relative to specific hypotheses. Results Collected dispersal distance and mass data spanned 9 and 21 orders of magnitude, respectively. Active dispersers dispersed significantly farther ( P P Conclusions Size is important to maximal dispersal distance for active dispersers, but not for passive dispersers. Claims that microbes disperse widely cannot be tested by current data based on direct observations of dispersal: indirect approaches will need to be applied. Distance–mass relationships should contribute to a resolution of neutral and niche‐based metacommunity theories by helping scale expectations for dispersal limitation. Also, distance–mass relationships should inform analyses of latitudinal species richness and conservation biology topics such as fragmentation, umbrella species and taxonomic homogenization.

Susceptibility of salmonid alphavirus to a range of chemical disinfectants - D A Graham; K Cherry; C J Wilson; H M Rowley (Journal of Fish Diseases, 2007)
A range of commercially available disinfectants were tested for efficacy against salmonid alphavirus under a range of different conditions including variations in concentration, temperature, contact time, water type and presence or absence of organic matter. Testing was based on the protocol defined in the draft European Standard prEN 14675, for which the effective standard is a 4 log (10) reduction in viral titre. All disinfectants were found to be effective under at least some of the conditions tested. However, the presence of organic matter in particular was shown to be detrimental in some cases, either through rendering some disinfectants ineffective, or by production of a visible inhomogeneity.

Quantitative trait loci for phytate in rice grain and their relationship with grain micronutrient content - James C. R. Stangoulis; Bao-Lam Huynh; Ross M. Welch; Eun-Young Choi; Robin D. Graham (Euphytica, 2007)

Modelling the role of intracolonial genetic diversity on regulation of brood temperature in honey bee (Apis mellifera L.) colonies - S. Graham; M. R. Myerscough; J. C. Jones; B. P. Oldroyd (Insectes Sociaux, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

Domain Formation in DODAB–Cholesterol Mixed Systems Monitored via Nile Red Anisotropy - Graham Hungerford; Elisabete M. S. Castanheira; Adelina L. F. Baptista; Paulo J. G. Coutinho; M. Elisabete C. D. Real Oliveira (Journal of Fluorescence, 2005)

An assessment of European pig diversity using molecular markers: Partitioning of diversity among breeds - Louis Ollivier; Lawrence Alderson; Gustavo C. Gandini; Jean-Louis Foulley; Chris S. Haley; Ruth Joosten; Annemieke P. Rattink; Barbara Harlizius; Martien A. M. Groenen; Yves Amigues; Marie-Yvonne Boscher; Geraldine Russell; et al. (Conservation Genetics, 2005)

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Factors Affecting the Fate of Ciprofloxacin in Aquatic Field Systems - L. A. Cardoza; C. W. Knapp; C. K. Larive; J. B. Belden; M. Lydy; D. W. Graham (Water, Air, & Soil Pollution, 2005)

Cataract Extraction and Risk of Breast Cancer - Shumin M. Zhang; Walter C. Willett; Frank B. Hu; Edward L. Giovannucci; JoAnn E. Manson; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2004)

Acetate non-utilizing mutants of Arabidopsis: evidence that organic acids influence carbohydrate perception in germinating seedlings - M. A. Hooks; J. E. Turner; E. C. Murphy; I. A. Graham (Molecular Genetics and Genomics, 2004)

Identification of Differentially Expressed Transcripts from Maturing Stem of Sugarcane by in silico Analysis of Stem Expressed Sequence Tags and Gene Expression Profiling - Rosanne E. Casu; Christine M. Dimmock; Scott C. Chapman; Christopher P.L. Grof; C. Lynne McIntyre; Graham D. Bonnett; John M. Manners (Plant Molecular Biology, 2004)

European climate in the late twenty-first century: regional simulations with two driving global models and two forcing scenarios - J. Räisänen; U. Hansson; A. Ullerstig; R. Döscher; L. P. Graham; C. Jones; H. E. M. Meier; P. Samuelsson; U. Willén (Climate Dynamics, 2004)

Correlates of horn and antler shape in bovids and cervids - T. M. Caro; C. M. Graham; C. J. Stoner; M. M. Flores (Behavioral Ecology and Sociobiology, 2003)

Characterization and evaluation of North American Trifolium ambiguum -nodulating rhizobia - M.-S. Beauregard; P. Seguin; C. C. Sheaffer; P. H. Graham (Biology and Fertility of Soils, 2003)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Probing Si and Ti Based Sol-Gel Matrices by Fluorescence Techniques - Graham Hungerford; Mário Rui Pereira; João A. Ferreira; Teresa M. R. Viseu; Anabela F. Coelho; M. Isabel; C. Ferreira; Klaus Suhling (Journal of Fluorescence, 2002)

Mechanisms of benthic prey capture in wrasses (Labridae) - L. A. Ferry-Graham; P. C. Wainwright; M. W. Westneat; D. R. Bellwood (Marine Biology, 2002)

Removal of a cysteine ligand from rubredoxin: assembly of Fe2S2 and Fe(S-Cys)3(OH) centres - Maddalena Cross; Zhiguang Xiao; Estelle M. Maes; Roman S. Czernuszewicz; Simon C. Drew; John R. Pilbrow; Graham N. George; Anthony G. Wedd (JBIC Journal of Biological Inorganic Chemistry, 2002)

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)

Scanning for telomeric deletions and duplications and uniparental disomy using genetic markers in 120 children with malformations - M. Rosenberg; C. Killoran; L. Dziadzio; S. Chang; D. Stone; J. Meck; D. Aughton; L. Bird; J. Bodurtha; S. Cassidy; J. Graham; A. Grix; et al. (Human Genetics, 2001)

Gene structure, alternative splicing, and chromosomal localization of pro-apoptotic Bcl-2 relative Bim - Philippe Bouillet; Li Chen Zhang; David C.S. Huang; Graham C. Webb; Cynthia D.K. Bottema; Paul Shore; Helen J. Eyre; Grant R. Sutherland; Jerry M. Adams (Mammalian Genome, 2001)

Zinc fertilisation increases tolerance to Rhizoctonia solani (AG 8) in Medicago truncatula - Tania C. Streeter; Zdenko Rengel; Stephen M. Neate; Robin D. Graham (Plant and Soil, 2001)

Monitoring the Phase Transition of C12E5/Water/Alkane Microemulsions Through Excimer Formation - M. E. C. D. Real Oliveira; Graham Hungerford; E. M. S. Castanheira; M. da G. Miguel; H. D. Burrows (Journal of Fluorescence, 2000)

The correlation of reaction and isotope fronts and the mechanism of metamorphic fluid flow - A. D. L. Skelton; J. W. Valley; C. M. Graham; M. J. Bickle; A. E. Fallick (Contributions to Mineralogy and Petrology, 2000)

ADRENAL FUNCTION IN WILD AND REHABILITATED PACIFIC HARBOR SEALS ( PHOCA VITULINA RICHARDII ) AND IN SEALS WITH PHOCINE HERPESVIRUS‐ASSOCIATED ADRENAL NECROSIS - F. M. D. Gulland; M. Haulena; L. J. Lowenstine; C. Munro; P. A. Graham; J. Bauman; J. Harvey (Marine Mammal Science, 1999)
A bstract Adrenal function in harbor seals ( Phoca vitulina richardii ) was evaluated using adrenocorticotrophic hormone (ACTH) stimulation tests and fecal cortisol levels. The effect of ACTH administration on plasma cortisol and aldosterone levels in five free‐living and 14 rehabilitated harbor seal pups was determined using enzyme immunoassay and radioimmunoassay, respectively. In free‐living seals, injection of ACTH caused a significant increase in mean plasma cortisol but not of mean aldosterone levels 60 min postinjection. In these seals, mean initial plasma aldosterone was significantly higher than initial levels in rehabilitated seals, while initial cortisol levels were similar. Of the rehabilitated seals, eight died with adrenal cortical necrosis associated with herpesvirus inclusions, while six lived to be released. In the seals that were released, both mean initial cortisol levels and response to ACTH decreased through rehabilitation. In the seals that died, mean initial cortisol and response to ACTH increased through rehabilitation. The differences between initial cortisol levels in seals that lived and those that died were significant at weeks two and four of rehabilitation but not at the week of admission. There was considerable individual variation in initial plasma aldosterone levels and responses to ACTH, although initial aldosterone levels were significantly higher in rehabilitated seals that died than in seals that lived. Seals with adrenal necrosis associated with herpesvirus infection did not have decreased adrenal hormone responses to ACTH. Differences between initial hormone levels and responses to ACTH in different groups of seals may be associated with differing stress levels. Fecal cortisol assays were not a useful method of assessing adrenal function in these seals, as measured levels did not correlate with plasma cortisol levels.

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.

Neutral lipids in macroalgal spores and their role in swimming - D. C. Reed; M. A. Brzezinski; D. A. Coury; W. M. Graham; R. L. Petty (Marine Biology, 1999)

Immunohistochemical localisation of α 1B -adrenergic receptors in the rat iris - T. Hilton Grayson; Jane M. Ellis; Songhai Chen; R. M. Graham; R. Dale Brown; C. E. Hill (Cell and Tissue Research, 1998)

Assignment of the growth hormone receptor gene to band q17 of the homeologous sheep 16 and cattle 20 chromosomes - Yvonne M. Parsons; Graham C. Webb; Cynthia D. K. Bottema (Mammalian Genome, 1998)

Cytokinesis and nodal anatomy in the charophycean green alga Chara zeylanica - M. E. Cook; L. E. Graham; C. A. Lavin (Protoplasma, 1998)

Comparing Environmental Conditions Using Indicators of Pollution Hazard - Graham W. Turner; Rod M. C. Ruffio (Environmental Management, 1997)

Periderm and lenticel characterization in relation to potato cultivar, soil moisture and tuber maturity - D. N. Tyner; M. J. Hocart; J. H. Lennard; D. C. Graham (Potato Research, 1997)

Novel approach to investigate a source of microbial contamination of central venous catheters - T. S. J. Elliott; H. A. Moss; S. E. Tebbs; I. C. Wilson; R. S. Bonser; T. R. Graham; L. P. Burke; M. H. Faroqui (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Volumetric studies of spheroids and left ventricles - J. M. Bateman; T. C. Rhea; T. P. Graham (Annals of Biomedical Engineering, 1982)

Chemical and enzymological characterization of an indonesian variant of human erythrocyte carbonic anhydrase II, CAIIJogjakarta (17 Lys ? Glu) - Graham L. Jones; A. Salam M. Sofro; Denis C. Shaw (Biochemical Genetics, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Acidification of “dry” caustic peeling waste by lactic acid fermentation - M. Gee; C. C. Huxsoll; R. P. Graham (American Journal of Potato Research, 1974)

Report of the Late Blight Investigations Committee - M. E. Gallegly; W. A. Hodgson; W. R. Mills; J. S. Niederhauser; J. R. Wallin; C. J. Eide; K. M. Graham (American Journal of Potato Research, 1961)

Report of the late blight investigating committee - John Niederhauser; W. R. Mills; R. Bonde; J. L. Howatt; L. C. Peterson; Keith Graham; M. E. Gallegly; C. J. Eide (American Journal of Potato Research, 1958)